Kajian Bentuk Dinding Dermaga Untuk Mereduksi Refleksi Gelombang = Study on Quaywall Shapes for Reducing Wave Reflections - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT Wave disturbance in many harbours can increase significantly due to reflections from breakwaters and other harbour structures including quay. Vertical walls which are often chosen, could cause high reflections. Interference of incident and reflected waves makes loading-unloading difficult, and often dangerous for smaller vessels. Therefore, design of low reflection quaywalls as an alternative. constructions to secure appropriate calmness of basin in both ordinary sea conditions or storm is nedeed. The aim of this research was to examine the non-convensional quaywall to reduce reflected waves. This was done by conducting physical model tests. The influence of some parameters on the reflected waves absorption was studied. Quaywalls made from iron post with various gap width between post and 1:2 sloping crushed stone structure were studied. Regular waves having various wave heights and periods were used for the investigation. The result of the research showed that the reflected waves was partly affected by gap width between post, post width, and sloping crushed stone structure. Wave absorption was also significantly affected by the period and the height of the incoming waves. Reflection coefficient minimum for iron bar with gaps and crushed stone were between 0.24 and 0.35. For iron bar only the reflection coefficient minimum was between 0.32 and 0.46.